Antioxidant capacity, total phenolic, carotenoid, and vitamin C contents of five table grape varieties from Algeria and their correlations - Farida Derradji-Benmeziane; Rachid Djamai; Yves Cadot (OENO One, 2014)
Aim: The aim of this work was the determination of some antioxidants (total polyphenols (TPP), total flavonoids (TF), carotenoids, vitamin C, the antioxidant capacity (AC) (reducing power) and other physicochemical parameters, such as pH, total soluble solids (°Brix), total acidity and density, in an attempt to understand how the evaluated characteristics vary with different grape varieties. Methods and results: Grape is currently known as a fruit that presents a very high antioxidant activity that can inhibit the harmful effects of free radicals. In this study, five Algerian table grape varieties were tested : Cardinal, Gros noir, Muscat noir, Muscat blanc and Victoria. TPP, TF, carotenoids and AC were determined by using colorimetric assays, and the physicochemical parameters (pH, °Brix, total acidity and density) were measured using classical methods. The darker varieties (Gros noir and Muscat noir) had the highest levels of polyphenols, flavonoids, carotenoids and vitamin C and possessed a good reducing power. A strong positive correlation was found, especially between TPP, TF and AC. Conclusion: This study indicated that some Algerian grape varieties exhibit high antioxidant phenolic and carotenoid content, which can potentially be used as natural source of antioxidant. Significance and impact of the study: This study on the AC, the TPP, carotenoid and vitamin C contents of five table grape varieties from Algeria and their correlations is very unique, as it is the first study on varieties grown in this country.